Thursday

January 29, 2015

January 29, 2015

Posted by **sh** on Wednesday, December 8, 2010 at 8:10pm.

f(x)=e^x - x

lim x->infinity (e^x)-x= infinity

when it's going towards infinity, shouldn't it equal to negative infinity, since 0-infinity = - infinity

lim x-> -infinity (e^x)-x= infinity

**Answer this Question**

**Related Questions**

Math - 1. If -1/infinity = infinity or -infinity ? 2. If lim x->infinity^- = ...

Math - 1. If -1/infinity = infinity or -infinity ? 2. If lim x->infinity^- = ...

Calc. Limits - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0...

calc - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- ...

Calc Please Help - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/...

MATH - I have been trying to do this problem for a couple of days but i cant ...

calculus - interval of convergence - infinity of the summation n=0: ((n+2)/(10^n...

calculus - interval of convergence - infinity of the summation n=0: ((n+2)/(10^...

math - i really dont understand why this 1-lim 3/(y+4) [the lim is x->...

Pre-cal - Please determine the following limits if they exist. If the limit does...